Corporate Finance in the Euromarkets and the Economics of Intermediation. - Davis, E; Mayer, C (CEPR, 1991)
This paper examines bond and syndicated bank finance in the Euromarkets. It uses a comprehensive data bank on Euromarkets to evaluate alternative theories of financial intermediation. A model is estimated that provides a good description of firms' choice of finance. The paper concludes that Euromarkets are best described by control ('transactions banking') rather than commitment ('relationship banking'). Bank and bond markets are not perfect substitutes, however, even for large companies: the financing of high-risk projects requires the involvement of banks. Banks therefore retain a central function and the operation of bank syndicates is crucial to the financing of large corporations.